The experiment of physical education teaching style on different categories of student confidence to improve the swimming learning value (Experimental method using design of treatment by factorial 3x2) at Higher School Of Teacher Training And Pedagogy Kusumanegara Jakarta - Saputra, Surya Adi; Sukur, Abdul; Tangkudung, James; Dlis, Firmansyah; Widiastuti, Widiastuti (Journal of Education, Health and Sport, 2019)
Purpose: This study aimed to solve the problem of 80% students swimming learning value are failed, the researcher tries to experiment and prove the most suitable physical education teaching style to improve students swimming learning value for physical education student college at Higher School Of Teacher Training And Pedagogy Kusumanegara Jakarta. There are 3 types of physical education teaching style (Training teaching style, Command teaching style, and Self-check teaching style), confidence as a moderator variable are divided into two parts (high confidence and low confidence)Methods: The quantitative experimental method was using design of treatment by factorial 3x2, participant were 60 male students divided into 6 groups, each consisting of 10 students. Before analyzing the hypothesis, there are 2 requirements tests: normality test by Liliefors and homogenity test by Levene’s Test. Second stage, hypotheses analyzed using variance analysis techniques (ANOVA) One-way Anava and Two-way Anava by significance α =0,05.Results: The results of this study indicate that the: (1) Teaching style has an influence on increasing swimming learning value for students college (2) There are "Differences" between teaching styles (Training teaching style, Command teaching style, Self-Check teaching style). (3) There is an "Interaction" between teaching style and confidence toward increasing the swimming learning value, (4) The Training teaching style is the most appropriate teaching style to improve the swimming learning value (5) For students in the category High Confidence more suitable to be taught with Training teaching style but For students in the category Low Confidence more suitable to be taught with Self-Check teaching style.Conclusion: To increasing the value of swimming learning value can be improved by Teaching styles for physical education students college.